A constructivist interpretation of the kantian principle of right and of the idea of the original contract (2013)
The main purpose of this article is to carry out a constructivist analysis of the concept of law regarding two of the most important principles in Kant's political philosophy: the principle of right and the idea of the original contract. The article starts out with a brief presentation of the meaning of Kantian constructivism, and then goes on to analyze the concept of right and of the attributes that define citizenships: freedom, equality, and civil independence. Finally, it examines the Kantian conception of the original contract in order to demonstrate that, according to Kant, there are political duties of both right and virtue.